Coping Strategies Used by Aging Parental Caregivers of Adults With Autism Spectrum Disorder. Issue 1 (January 2021) - Marsack-Topolewski, Christina N.; Wilson, Kaitlyn P.
Caregiving can be a lifelong responsibility for parents of individuals with autism spectrum disorder (ASD). This study examined coping strategies and barriers experienced by parents of adult children with ASD. The 51 parents who participated in this study were at least 50 years old and had an adult child (18+) with ASD. Semistructured, one-on-one interviews were conducted with parents to understand their experiences of having an adult child with ASD. Using a qualitative, phenomenological approach, thematic analysis revealed seven themes related to parents' coping strategies or lack thereof. Themes discussed include faith/spirituality, physical activity/fitness, self-focused coping, work, acceptance, reliance on social support, and barriers to coping. Most parents discussed having at least one coping strategy, with some sharing multiple strategies.